Designing User-Friendly Grids for the Gender-Specification of Rural, Semi-Urban, and Urban School Toilets in West Africa: Lessons from the Republic of Benin - T. A. Kouévi; F. Okry; H. Kpangon; A. C. Kouévi; H. Amoukpo; L. Hounkpatin; E. Attakin; C. R. Tossou; E. Achigan-Dako; M-P. Kestemont (European Scientific Journal, ESJ, 2023)
Gender equity, quality education, and sanitation in rural and urban areas are widely considered as development imperatives. However, while many countries of the world are already far with the gendering of their schools’ toilets, most others still tend to systematically construct the same number of toilet cabins for female and male students, often ignoring specific needs associated with biophysical differences and disabilities among the students. This poor gendering of school toilets prevailed in the Republic of Benin until 2013, when, within the framework of the Pluriannual Water and Sanitation Programme (PPEA phase 2) funded by the Netherlands’ Ministry of Cooperation through its Embassy in the Republic of Benin, the Directorate of Hygiene and Sanitation of the Ministry of Public Health in collaboration with Water and Sanitation for Africa Agency, decided to launch a study for gender and disability specific toilets in primary and secondary schools. This original paper discusses the process towards the design of norms and grids for the calculation of toilet cabins and urinals needs of primary and secondary school students of rural, semi-urban, urban, Sahelian, Sudanian, lake, and coastal areas of the Republic of Benin. The study took place in four steps. The first step consisted of identifying key factors that affect the use of school toilets by students, especially female and disabled students. The second step consisted of observing and recording the use of school toilets by students, and building on those observations and records to estimate the number of toilet cabins and urinals required per agroecological and sociocultural area. The third step built on the results from the first and second steps to design simplified grids that allow sanitation and schools’ decision-makers to easily and quickly calculate the number of toilet cabins and urinals required for the target schools, per gender and disability. The fourth step consisted of building the capacities of potential users of the grids, for their relevant use. The findings indicate a variation of needs among primary and secondary schools, and the study zones, due to sociocultural and development differences. The grids have been in use in Benin since 2016 and it has easily helped to calculate gender-specific toilet needs in the study areas. After five years of use, their performance requires to be assessed for further adaptations. A further paper will report on the performance of these grids.